BASH: Biomechanical Animated Skinned Human for Visualization of Kinematics and Muscle Activity - Schleicher, Robert; Nitschke, Marlies; Martschinke, Jana; Stamminger, Marc; Eskofier, Björn; Klucken, Jochen; Koelewijn, Anne (Proceedings of the 16th International Joint Conference on Computer Vision, Imaging and Computer Graphics Theory and Applications - Volume 1: GRAPP, 2021)
Biomechanical analysis of human motion is applied in medicine, sports and product design. However, visualizations of biomechanical variables are still highly abstract and technical since the body is visualized with a skeleton and muscles are represented as lines. We propose a more intuitive and realistic visualization of kinematics and muscle activity to increase accessibility for non-experts like patients, athletes, or designers. To this end, the Biomechanical Animated Skinned Human (BASH) model is created and scaled to match the anthropometry defined by a musculoskeletal model in OpenSim file format. Motion is visualized with an accurate pose transformation of the BASH model using kinematic data as input. A statistical model contributes to a natural human appearance and realistic soft tissue deformations during the animation. Finally, muscle activity is highlighted on the model surface. The visualization pipeline is easily applicable since it requires only the musculoskeletal model, kinematics and muscle activation patterns as input. We demonstrate the capabilities for straight and curved running simulated with a full-body musculoskeletal model. We conclude that our visualization could be perceived as intuitive and better accessible for non-experts than conventional skeleton and line representations. However, this has to be confirmed in future usability and perception studies.<br
Keywords: Biomechanics; Surface Visualization; Animation; Statistical Human Model; Kinematics; Muscle Activity